Altemeier Rectosigmoidectomy for Strangulated Rectal Prolapse - Bhandari, R S; Lakhey, P J (Journal of Nepal Health Research Council, 2011)
A 70 year old gentleman presented in the emergency department of Tribhuvan University Teaching Hospital, Kathmandu, Nepal with strangulated complete rectal prolapse. After complete evaluation and necessary investigations, patient underwent Altemeier perineal rectosigmoidectomy and had an uneventful recovery. This case report tries to highlight the importance of Altemeier procedure as the only option for managing rectal prolapse when patients present with incarceration or strangulation of the prolapsed rectum with very good outcome. Keywords: altemeier, perineal, rectal prolapse, rectosigmoidectomy, strangulation.